Perspectives on comets, comet-like asteroids, and their predisposition to provide an environment that is friendly to life - Bosiek, Katharina; Hausmann, Michael; Hildenbrand, Georg Lars (Astrobiology, 2016)
In recent years, studies have shown that there are many similarities between comets and asteroids. In some cases, it cannot even be determined to which of these groups an object belongs. This is especially true for objects found beyond the main asteroid belt. Because of the lack of comet fragments, more progress has been made concerning the chemical composition of asteroids. In particular, the SMASSII classification establishes a link between the reflecting spectra and chemical composition of asteroids and meteorites.To find clues for the chemical structure of comets, the parameters of all known asteroids of the SMASSII classification were compared to those of comet groups like the Encke-type comets, the Jupiter-family comets, and the Halley-type comets, as well as comet-like objects like the damocloids and the centaurs. Fifty-six SMASSII objects similar to comets were found and are categorized as comet-like asteroids in this work.Aside from the chemistry, it is assumed that the available energy on these celestial bodies plays an important role concerning habitability. For the determination of the available energy, the effective temperature was calculated. Additionally, the size of these objects was considered in order to evaluate the possibility of a liquid water core, which provides an environment that is more likely to support processes necessary to create the building blocks of life. Further study of such objects could be notable for the period of the Late Heavy Bombardment and could therefore provide important implications for our understanding of the inner workings of the prebiotic evolution within the Solar System since the beginning.
Gesehen am 04.11.2019